2021
DOI: 10.1001/jamaoncol.2021.1262
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Stereotactic Radiosurgery for Brainstem Metastases

Abstract: IMPORTANCEOwing to the proximity to critical neurologic structures, treatment options for brainstem metastases (BSM) are limited, and BSM growth can cause acute morbidity or death. Stereotactic radiosurgery (SRS) is the only local therapy for BSM, but efficacy and safety of this approach are incompletely understood because patients with BSM are excluded from most clinical trials.OBJECTIVE To perform a systematic review and comparative meta-analysis of SRS studies for BSM in the context of prospective trials of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 55 publications
5
40
1
2
Order By: Relevance
“…However, the reported survival of SRS series might suggest a different scenario. In the present analysis, the median cancer-speci c survival was 14.6 months which is in line with previous evidence on BM patients 21 . By comparison the median survival in the study of Tri letti et al 24 was 5.6 months and the 1-year survival 32.7%.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the reported survival of SRS series might suggest a different scenario. In the present analysis, the median cancer-speci c survival was 14.6 months which is in line with previous evidence on BM patients 21 . By comparison the median survival in the study of Tri letti et al 24 was 5.6 months and the 1-year survival 32.7%.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the majority of these patients were treated with gamma-knife, with few data available for linear accelerator (linac)-based SRS. A recent systematic review and meta-analysis of those retrospective studies demonstrated the e cacy of SRS in the treatment of BSM; however, only few predictive parameters of treatment response were identi ed 21 . Therefore, it is hard to date to infer speci c recommendation on dose prescription, as well as the identi cation of predictive parameters, considering the limited available data 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Symptomatic lesions should be treated at the beginning of treatment to avoid worsening and because radiation, mainly SRS, and other local treatments can control symptoms quickly. A recent PRISMA analysis concluded SRS led to a symptom improvement of 55%, and these results compared favorably to trials of targeted or immunotherapy for BMs ( 233 ). Concerning painful metastasis, ablative radiotherapy is efficient but compared to conventional irradiation, comparisons have yielded contradictory results ( 234 , 235 ).…”
Section: Questions To Be Further Discussed and Consideredmentioning
confidence: 99%
“…Moreover, the majority of these patients were treated with gamma-knife SRS, with few data available for frameless linear accelerator (linac)-based SRS. A recent systematic review and meta-analysis of those retrospective studies demonstrated the efficacy of SRS in the treatment of BSM; however, only a few predictive parameters of treatment response were identified [22] . Therefore, it is hard to date to infer specific recommendations on dose prescription, as well as the identification of predictive factors of outcome because of the limited available data.…”
Section: Introductionmentioning
confidence: 99%